PENGARUH KOMPONEN RISK BASED BANK RATING TERHADAP HARGA SAHAM PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008-2012 (Students' Journal of Accounting and Banking, 2014)
The objectives of this research are knowing and analyzing the influence of RBBR component, in this case using Beta, Non Performing Loan, Loan Deposit Ratio, Komposite Self Assesment Good Corporate Governance, Capital Adequacy Ratio, and Return On Asset influence the stock price banking companies in Indoensia Stock Exchange. The population in this research is banking sector in the Indonesia Stock Exchange for years 2008 until 2012. The sample is defined by purposive sampling technique to get a representative sample appropriate with the criteria defined. There are 21 go public banking companies selected as sample for this research. This research was analyzed using multiple regressions. This research found the empirical results that partially, Beta, Non Performing Loan, Loan Deposit Ratio, Komposite Self Assesment Good Corporate Governance influences negative significant and Return On Asset positively significant to the stock price exchange banking companies in the in Indonesia Stock Exchange. While the result of partial test for Capital Adequacy Ratio showed that partially influence negative no significantly to the stock price. Keywords: Beta, Non Performing Loan, Loan Deposit Ratio, Komposite Self Assesment Good Corporate Governance, Capital Adequacy Ratio, dan Return On Asset and stock price